Wschodnia świadomość zła według Miłosza - Kaźmierczyk, Zbigniew (Acta Polono-Ruthenica, 2018)
The article shows the Eastern awareness of evil from the perspective of Miłosz. Its essence is the ability to differentiate the good from the evil when there is an inevitable conviction that evil is necessary. The ground for this conviction is laid in an aversion to the impulsive forces of a body and the inherent powers of matter, as well as in the inevitability of yielding to them. These are the forces and powers which constitute the blind will of domination of one over another in different dimensions. The article explains that in the Eastern awareness of evil the knowledge of human sinfulness is of religious nature. The one who does a wrong thing and is painfully aware of this fact, due to this awareness, prevails (according to Dostojewski and Miłosz) over a pretentious aesthete who thinks he or she is good by nature. The aware sinner prevails because he or she does not turn down the original sin, does not place the God-Human in the position of Human-God, and does not give the world to the land (does not exchange the Christian eschatology for the secular eschatology). The article demonstrates that Miłosz, in alliance with Dostojewski, attacks Polish culture for the alleged unawareness of evil; he realizes that the Manichean awareness of evil has a weak point: it turns a man away from the world of matter, nature, micro- and macrocosm. Hence, the Slavic people have so few practical achievements in making the land their subject in comparison to the accomplishments of the Western men. Moreover, the Eastern awareness of evil, as the awareness of superiority over the ethical waste of effort of an ordinary day, shows, according to Miłosz, an inclination for a messianic bearing of suffering - passively enduring the suffering like a Christian. That is the mistake made by Dostojewski. The article indicates that Miłosz enriches the Eastern awareness of evil with the Western affirmation of what is physical and material.